Avaliação da incorporação do rejeito do processo bayer em formulações com argila do município de Acará-Pa visando a produção de cerâmica vermelha - VAZ NETO, Josias de Souza (2023)
The state of Pará has consolidated itself as a power in the sense of opening new fronts for the use and processing of raw materials and giving space for a growth in the mining and metallurgy sector, however, this growth in development also results in the generation of tons of waste and rejects, which in certain aspects directly impact the environment and the surroundings of these industrial centers. This study focused on the production of red ceramics, using waste from the Bayer process, specifically red mud. A detailed analysis of the formulations and processing parameters, such as burning level and time, was conducted with the proposal to reintroduce this waste, adding value, also aiming at production with a focus on reducing the consumption of raw materials, while maintaining compliance with technical standards. To achieve this objective, this study was based on methodologies already used in the insertion of red mud in the production of ceramics, using a total of three different formulations LA8020 (80% Waste and 20% Clay), LA6040 (60% Waste and 40% Clay) and LA100 (100% Clay) as a comparison, in addition to three firing temperatures 900, 1000 and 1100 °C. The standards related to the development of red ceramics ABNT NBR 15270/2017 and ABNT NBR 15310/2005 were adopted, which classify ceramic products into specific categories, such as sealing blocks, structural blocks and ceramic tiles, as a parameter to evaluate the quality of the materials produced and usage classification. The results obtained indicated that in certain parameters the tested formulations met the requirements established by the standards. This can be achieved by varying the burning time and temperature, resulting in significant savings in production costs and more efficient use of raw materials. Furthermore, the results demonstrated the feasibility of producing materials with performance comparable to conventional products available on the market. It is important to highlight the LA6040 formulation as the most promising for the purposes of this study, as it exhibited a property profile that suggests a high potential for use in the development of red ceramics, making it suitable for the manufacture of sealing blocks or bricks.